CAFs exosomal miR-21-5p suppresses ferroptosis and promotes proliferation and migration in osteosarcoma - Xiaoying Niu; Wen Tian; Yuanmeng Ke; Yifan Li; Xinxin Zhang (Cancer Cell International)
Abstract Background Osteosarcoma is one of the malignant tumors in children and adolescents patients. Uncontrolled and unlimited proliferation and metastasis lead to poor overall survival. CAFs play a pivotal role in the osteosarcoma tumor microenvironment, exerting significant influence on prognosis and treatment outcomes. However, there remains a need for further exploration into the intricate molecular mechanisms underlying CAFs. Methods Single-cell RNA sequencing was employed to characterize the microenvironment of osteosarcoma. Tissue exosomal miRNA sequencing was conducted on tumor tissues and adjacent normal tissues to screen for abnormal expression of exosomal miRNAs. WGCNA analysis was used to identify target exosomal miRNAs. The relative expression of miR-21-5p was analyzed using qRT-PCR. The proliferation rate and migration ability of tumor cells were assessed using the CCK8 and Transwell method, respectively. Exosomes derived from cells were extracted and characterized via transmission electron microscopy and NTA analysis. siRNA interference was utilized to disrupt the expression of miR-21-5p in CAFs. Experiments in vivo validated the role of exosomal miR-21-5p in promoting malignant characteristics in osteosarcoma. Results Single-cell RNA sequencing analysis of GSE162454 revealed the crucial role of CAFs in the pathogenesis of osteosarcoma. Tissue exosomal miRNA sequencing unveiled significant differential expression of miR-21-5p. Subsequently, aberrant upregulation of exosomal miR-21-5p exhibited a strong correlation with advanced clinical stage and poor prognosis in osteosarcoma. Further experiments in vitro indicated that elevated levels of miR-21-5p significantly enhanced proliferation and migration of osteosarcoma cells by suppressing ferroptosis. Moreover, experiments in vivo validated the capacity of CAFs-derived exosomal miR-21-5p to promote tumor growth and weight, thereby demonstrating their ability to deliver miR-21-5p to osteosarcoma cells and induce proliferation and migration through inhibition of ferroptosis. Conclusions Our findings indicate that exosomal miR-21-5p could potentially serve as a therapeutic target in osteosarcoma, providing initial evidence for further clinical investigation. Graphical Abstract